THE IMPLEMENTATION OF DISASTER MITIGATION PLAN THROUGH STRUCTURAL FUNCTIONAL APPROACH - Muhammad Fedryansyah; Herijanto Bekti; Ramadhan Pancasilawan (Sosiohumaniora, 2020)
ABSTRACT. Pagerwangi Village is an area prone to natural disasters in West Bandung Regency. Also the geographical location is entered in the red-fault zone of the Lembang. So in the predictions will be one of the affected areas due to the tectonic earthquakes originating from the fault of the Lembang. Disaster management programs have been conducted by the Government along with other parties such as educational institutions and community groups. The study aims to analyse how the implementation of disaster mitigation through a functional structural approach or social balance theory of Talcott Parsons. The approach used on this studies is descriptive qualitative. The results showed that there were barriers in the system of functional structural approaches to disaster mitigation in the area of the Pagerwangi village of the four aspects namely integration, adaptation, latency and goal attaintment. These obstacles occur from one aspect, which affects other aspects.